Rosszkedvünk tana: Értelem, érzelem, közgazdaság-tudomány - Károly Fazekas (Hungarian Academy of Sciences, Institute of Economics, 2015)
– It is our natural inclination to find stable patterns and meaning in the chaotic world around us. This assists in our efforts to understand the past and forecast the future. The starting point of this essay is the phrase "dismal science" which is an often used 'epitheton ornans' of economics. While this essay retraces the origins of this epithet it also sheds light on the differences in interpretation of the dominant forces that shape our economy and society. The stories evoked from the age of industrial revolution, such as the "Carlyle-Mill Debate"and the "Edward Erye-William Gordon Controversy", point out the necessary coincidence of three main ingredients of modern economic growth. The first is the essential legal framework of the free market economy, the second is the rule of law - one of the main institutional prerequisites of a competitive economy, the third is the change in rhetoric concerning the much needed requisites of the market economy such as the principle of private property, free trade, unfettered entrepreneurship and fair labour market relations. We emphasize the dominant roles of those individuals who carry the burden for the consistent representation of these values both in the academic sphere and in civil society.
Keywords: N3; O1; Z1; 330; dismal science; Thomas Carlyle; John Stuart Mill; economic history; political economics; modern economic growth; institutions; rhetoric